DASAR-DASAR DAN RUANG LINGKUP EVALUASI PENDIDIKAN - Tanwir Tanwir (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
Evaluation must be implemented systematically and continuously in order to describe the ability of the students. The main mistakes that often occur among teachers is that evaluation is carried out at certain moments, such as at the end of the unit, middle, and end of a teaching program. As a result of that is the lack of information about the students, causing many teachers prediction is biased in determining their position in class activities. Evaluation should not only be concidered as a collection of techniques but also rather a process that is based on principles. What should be assessed always gives priority in the process of evaluation. The interesting problem that is discussed in this paper is about the basics and the scope of educational evaluation.